EVALUATION OF Sapindus trifoliatus ON ALZHEIMER'S DISEASE INDUCED BY ALUMINUM CHLORIDE IN RATS - NIM BAHADUR DANGI; B.SREEDHAR NAIK; S.NAGARJUNA; ANIL SHRESTHA; HARI PRASAD SAPKOTA; NABIN WAGLE (International Journal of Pharma and Bio Sciences, 2015)
The present study aimed to investigate the possible prophylactic and therapeutic effects of hydro-alcoholic extract of Sapindus trifoliatus on AD induced by AlCl3 in rats. In this study thirty adult Wistar albino rats were selected and were divided into 5 groups (six each). Group I, II, III, IV & V served as normal control, negative control, test group and standard control respectively. The rats were given treatment for 30 days and behavioural parameters were determined on 1st, 10th, 20th, &30th day of treatment. After day 30th rats were sacrificed and biochemical parameters (antioxidant levels & Acetylcholinesterase activity) were determined. This study indicated that Sapindus trifoliatus when was used for treatment of AlCl3induced AD, it improves the behavioural & biochemical parameters. The histopathological finding in hippocampus of brain tissue neuron appears less or more like normal one when compared to the negative control